Complex networks : structure, robustness, and function - Cohen, Reuven, 1974-; Havlin, Shlomo (New York : Cambridge University Press, 2010)
'Examining important results and analytical techniques, this graduate-level textbook is a step-by-step presentation of the structure and function of complex networks. From the stability of the Internet to efficient methods of immunizing populations, from the spread of epidemics to how to search efficiently for individuals, this textbook explains the theoretical methods used, and the experimental and analytical results obtained. Ideal for graduate students entering this field, it gives detailed derivations of many results in complex networks theory. End-of-chapter review questions help students monitor their understanding of the materials presented'--
Machine generated contents note: 1. Introduction; Part I. Random Network Models: 2. The Erdos-Renyi models; 3. Observations in real-world networks; 4. Models for complex networks; 5. Growing network models; Part II. Structure and Robustness of Complex Networks: 6. Distances in scale-free networks - the ultra small world; 7. Self-similarity in complex networks; 8. Distances in geographically embedded networks; 9. The network's structure - the generating function method; 10. Percolation on complex networks; 11. Structure of random directed networks - the bow tie; 12. Introducing weights - bandwidth allocation and multimedia broadcasting; Part III. Network Function - Dynamics and Applications: 13. Optimization of the network structure; 14. Epidemiological models; 15. Immunization; 16. Thermodynamic models on networks; 17. Spectral properties, transport, diffusion and dynamics; 18. Searching in networks; 19. Biological networks and network motifs; Part IV. Appendices; References; Index.
Includes bibliographical references and index.
Keywords: System analysis